Private Lives, Public Deaths : Antigone and the Invention of Individuality - Strauss, Jonathan (Book collections on Project MUSE., 2013)
Here, the author shows how Sophocles' tragedy Antigone crystallized the political, intellectual, and aesthetic forces of an entire historical moment - fifth-century Athens - into one idea: the value of a single, living person.